2021
DOI: 10.3390/ani11041042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gonadal Transcriptomes Uncovers Reproduction-Related Genes with Sexually Dimorphic Expression Patterns in Diodon hystrix

Abstract: Diodon hystrix is a new and emerging aquaculture species in south China. However, due to the lack of understanding of reproductive regulation, the management of breeding and reproduction under captivity remains a barrier for the commercial aquaculture of D. hystrix. More genetic information is needed to identify genes critical for gonadal development. Here, the first gonadal transcriptomes of D. hystrix were analyzed and 151.89 million clean reads were generated. All reads were assembled into 57,077 unigenes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
2
12
0
Order By: Relevance
“…Hsd17b7 could convert estrone to E 2 and played an important role in mouse embryonic development [ 52 ]. The expression levels of cyp11a , hsd3b , and hsd11b2 were observably higher in male P. sinensis than in the female, which was consistent with the results of Oryzias latipes [ 53 ]. However, the expression level of hsd17b7 was inconsistent with that reported in previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Hsd17b7 could convert estrone to E 2 and played an important role in mouse embryonic development [ 52 ]. The expression levels of cyp11a , hsd3b , and hsd11b2 were observably higher in male P. sinensis than in the female, which was consistent with the results of Oryzias latipes [ 53 ]. However, the expression level of hsd17b7 was inconsistent with that reported in previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have capitalized on this powerful tool to analyze the holistic expression patterns in gonads. For instance, the gonad transcriptome of Nile tilapia, Oreochromis niloticus (Tao et al, 2013;Sun et al, 2018;Teng et al, 2020;Lin et al, 2021a), adult spotted scat (He et al, 2019), Chinese tongue sole, Cynoglossus semilaevis (Wang et al, 2019), silver sillago, Sillago sihama (Tian et al, 2019), Hong Kong catfish, Clarias fuscus (Lin et al, 2021b), spot-fin porcupine fish, Diodon hystrix (Chen et al, 2021) and others (Santos et al, 2007;Dıáz et al, 2014;Chen et al, 2021;Kohli et al, 2021;Yao et al, 2021;Zhu et al, 2022), revealed numerous differential and male and female pathway genes. As indicated above, previous studies identified several sex-related genes in adult spotted scat by gonadal transcriptomics (He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, technological advancements such as transcriptome analysis have made identifying gonadal sexual biased genes easy. Numerous sex-biased genes have since been identified in many other species [ 41 , 42 , 53 , 54 , 55 ], including Nile tilapia [ 40 ] and spotted scat [ 36 ]. Meanwhile, most of these studies have focused on gonadal gene expression, with little or no interest in the possible mechanism leading to sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed various transcriptome data for gonadal tissues to understand the expression patterns of the Dmrt2a & b in different species. Either zebrafish or spotted scat Dmrt1 , Dmrt2a , and Dmrt2b transcripts were used as query sequences to blast the transcriptome data (cds) of spotted scat [ 36 ], Hainan medaka ( Oryzias curvinotus ) [ 38 ], silver sillago ( Sillago sihama ) [ 39 ], Nile tilapia ( Oreochromis niloticus ) [ 40 ], Hong Kong catfish ( Clarias fuscus ) [ 41 ], and spot-fin porcupine fish ( Diodon hystrix ) [ 42 ]. For confirmation, the results with different transcript numbers and maximum hits were blasted using NCBI nucleotide blast ( , accessed on 15 October 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation